2012
DOI: 10.1097/bsd.0b013e31823972d4
|View full text |Cite
|
Sign up to set email alerts
|

The Pedicle-facet Angle and Tropism in the Sagittal Plane in Degenerative Spondylolisthesis

Abstract: The P-F angle was the highest at L4-L5 both in the DS and the control group, which might explain the fact that L4 vertebra is more likely to slip forward. The P-F angle of the slipped vertebra alone was more horizontally inclined and facet tropism in the sagittal plane may relate well to DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…It has been shown that increased angles might predispose to slippage and degeneration [8]. Our data show larger angles in symptomatic patients.…”
Section: Facet Joint Anglesupporting
confidence: 60%
See 2 more Smart Citations
“…It has been shown that increased angles might predispose to slippage and degeneration [8]. Our data show larger angles in symptomatic patients.…”
Section: Facet Joint Anglesupporting
confidence: 60%
“…Besides intervertebral disc degeneration, infection or fracture, degenerative changes in the posterior stabilizing column (facet joints, interspinous ligaments and paraspinal muscles) may be the cause of low back pain [7]. Degenerative spondylolisthesis is common and may become more important with aging populations [8]. The proportion of patients with low back pain in whom facet joints are causative has been estimated to be 5-15% [9] has been shown to increase with age [10] and may amount up to 50% in chronic pain cohorts [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al [12] showed in their study in 2012 on 156 patients that facet joint tropism was significantly greater in these patients compared with control subjects. In one of the largest studies in asia-pacific region by Samartzis et al [13] in 2016, assessing facet joint orientation in patients with spondylolisthesis, it was concluded that greater sagittal facet joint angulation was associated with L4-L5 spondylolisthesis.…”
Section: Discussionmentioning
confidence: 92%
“…Individuals with sagitally oriented facet joints have therefore been regarded as prone for development of DS. 2,8 Facet tropism is defined as asymmetry between left and right facet joint orientation, a difference of 8° or more is considered as tropism. 9 Recently, there have been multicentre studies 9,10 on this topic, however, the scope of these studies was limited by the fact that they did not include any control group without DS at any level.…”
Section: Introductionmentioning
confidence: 99%